PENGARUH LKS BERORIENTASI PENDEKATAN SAINTIFIK DALAM METODE QUANTUM LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA NEGERI 2 PADANG - Desestra Desestra; Hufri Hufri; Fatni MUfit (Universitas Negeri Padang, 2015)
The background of this research is still at least a scientific approach oriented teaching materials including student worksheet (LKS) and learning methods that are less attractive, including of SMA state 2 Padang. In curriculum requires tecahers to be able to utilize the entire potensial of the students in the teaching, so that the student centered learning. One approach with regard to these demands is the scientific approach, so that learning can be implemented with either the necessary teaching materials and methods that support the learning process. This purpose of research to investigate the influence of LKS oriented scientific approach in the method of quantum learning to learning outcomes-physics class X students of SMA state 2 Padang in the school year 2014/2015. This type of research is a